High-throughput multiphoton-induced three-dimensional ablation and imaging for biotissues - Lin, Chun-Yu (Biomed Opt Express, 2015)
In this study, a temporal focusing-based high-throughput multiphoton-induced ablation system with axially-resolved widefield multiphoton excitation has been successfully applied to rapidly disrupt biotissues. Experimental results demonstrate that this technique features high efficiency for achieving large-area laser ablation without causing serious photothermal damage in non-ablated regions. Furthermore, the rate of tissue processing can reach around 1.6 × 10(6) μm(3)/s in chicken tendon. Moreover, the temporal focusing-based multiphoton system can be efficiently utilized in optical imaging through iterating high-throughput multiphoton-induced ablation machining followed by widefield optical sectioning; hence, it has the potential to obtain molecular images for a whole bio-specimen.